Association Between HbA1c Level and Renal Function Markers in Patients with Diabetes Mellitus - Muhammadiy, Noer Sidqi; Purniawan, Luki Herli; Afthoni, Muhammad Hilmi (Journal of Indonesian Medical Laboratory and Science, 2025)
Background: Diabetes mellitus (DM) is a major contributor to kidney failure worldwide. Glycated haemoglobin (HbA1c) is widely recognised as a marker for glycemic regulation, yet its association with renal function decline is not fully clarified. Objective: This study investigates the association between HbA1c levels and renal function indicators, namely creatinine, urea, and microalbumin, in individuals with DM. Materials and Methods: A cross-sectional approach was utilised, analysing retrospective data collected from the medical records of DM patients participating in the Prolanis program in Bondowoso Regency during 2024. Correlation tests and linear regression were used to determine the relationship between HbA1c and the selected renal parameters, with a statistical significance threshold of p < 0.05. Results: Most patients exhibited HbA1c levels and renal parameters within normal limits. Nonetheless, a statistically significant positive correlation was identified between elevated HbA1c levels and increased concentrations of creatinine (p = 0.020), urea (p = 0.01), and microalbumin (p = 0.01). Conclusion: Higher HbA1c levels are associated with deteriorating kidney function among DM patients. However, HbA1c should not be solely relied upon as a standalone marker for renal impairment. Further investigations are necessary to elucidate the biological pathways involved and to evaluate the potential of HbA1c control in mitigating kidney disease progression.